Genome-Wide Identification of GDSL-Type Esterase/Lipase Gene Family in Dasypyrum villosum L. Reveals That DvGELP53 Is Related to BSMV Infection - Heng Zhang (MDPI AG, 2021)
GDSL-type esterase/lipase proteins (GELPs) characterized by a conserved GDSL motif at their N-terminus belong to the lipid hydrolysis enzyme superfamily. In plants, GELPs play an important role in plant growth, development and stress response. The studies of the identification and characterization of the GELP gene family in Triticeae have not been reported. In this study, 193 DvGELPs were identified in Dasypyrum villosum and classified into 11 groups (clade A–K) by means of phylogenetic analysis. Most DvGELPs contain only one GDSL domain, only four DvGELPs contain other domains besides the GDSL domain. Gene structure analysis indicated 35.2% DvGELP genes have four introns and five exons. In the promoter regions of the identified DvGELPs, we detected 4502 putative cis-elements, which were associated with plant hormones, plant growth, environmental stress and light responsiveness. Expression profiling revealed 36, 44 and 17 DvGELPs were highly expressed in the spike, the root and the grain, respectively. Further investigation of a root-specific expressing GELP, DvGELP53, indicated it was induced by a variety of biotic and abiotic stresses. The knockdown of DvGELP53 inhibited long-distance movement of BSMV in the tissue of D. villosum. This research provides a genome-wide glimpse of the D. villosum GELP genes and hints at the participation of DvGELP53 in the interaction between virus and plants.